PEMANFAATAN LIMBAH AMPAS TEBU SEBAGAI ADSORBEN UNTUK PENINGKATAN KUALITAS AIR GAMBUT - Patricia Lucky Yoseva; Akmal Muchtar; Halida Sophia (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Sugarcane bagasse contains various biomass compounds, like cellulose and lignin,which has the potential to be converted into a source of carbon for the adsorption process. This study was aimed to use carbonized bagasse powder as an adsorbent toincrease quality of peat water. Bagasse powder was carbonizied at 300 o C for 2,5 hoursand sieved using a sieve storied 100 and 200 mesh. Carbonizied bagasse powder wascharacterize in terms of moisture content, ash content, I 2 adsorption capacity, surfacearea and functional groups determination using FTIR. Adsorption process was observedby mass variations (0,5; 1; 1, 5; 2 grams) then at the mass maximum (2 gram) wascontinued by contact time variations (30, 60, 90, 120 minutes). Parameters of this studywere analyzed such as odor, colour, pH, turbidity, TDS, TSS, metal content of Fe andhumic acid in peat water. All of the results were compared to PERMENKES RI “AboutRequirement and Water Quality Control” No.416/MENKES/PER/IX/1990. The analysisresult showed that variation of contact time does not affect all parameters that have beenanalyzed. After compared to PERMENKES RI only odor, turbidity, TDS, content of Fe(2 grams; 120 minutes) fulfilled the standar, respectively (18,2 NTU; 54,15%),(98 mg/L; 52,65%), and (0,128 mg/L; 52,65%).